How to walk on water lifting the veil on evolution from terrestrial to water walking insect. (Research'eu results magazine)
Anyone who has seen a lake or a small pond will have witnessed the evolutionary marvel of those curious insects that run over water with no trouble whatsoever, as if it were solid ground. An EU project is allowing ENS de Lyon to investigate the genetics behind this capacity.